2001
DOI: 10.1021/jp0119173
|View full text |Cite
|
Sign up to set email alerts
|

Novel Resonance Raman Enhancement of Local Structure around Solvated Electrons in Water

Abstract: Picosecond time-resolved Raman spectra of water were measured under the resonance condition with the s f p electronic transition of the solvated electron for the first time. We found that a strong transient Raman band appears in the frequency region 30 cm -1 lower than the OH-bend band of bulk water in accordance with the formation of solvated electrons. The observed transient Raman band was assigned to the vibration of the solvating water molecules that strongly interact with the solvated electron in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 23 publications
6
59
0
Order By: Relevance
“…35 First, they assumed that the GSB component was the same as the equilibrium absorption spectrum and did not change with time. This assumption has been tested by multiple TA, 56,59 photon echo, 38,60 and resonance Raman [61][62][63] experiments, all of which verify that the ground-state absorption of the hydrated electron is homogeneously broadened so there indeed should be no spectral diffusion in the GSB. Second, Barbara and co-workers assumed that the spectrum of the HGS electron was the same as that of an equilibrium hydrated electron but at a higher effective temperature and that this effective temperature relaxed exponentially with time.…”
Section: A Modeling the Hydrated Electron's Lifetime With Transient mentioning
confidence: 95%
“…35 First, they assumed that the GSB component was the same as the equilibrium absorption spectrum and did not change with time. This assumption has been tested by multiple TA, 56,59 photon echo, 38,60 and resonance Raman [61][62][63] experiments, all of which verify that the ground-state absorption of the hydrated electron is homogeneously broadened so there indeed should be no spectral diffusion in the GSB. Second, Barbara and co-workers assumed that the spectrum of the HGS electron was the same as that of an equilibrium hydrated electron but at a higher effective temperature and that this effective temperature relaxed exponentially with time.…”
Section: A Modeling the Hydrated Electron's Lifetime With Transient mentioning
confidence: 95%
“…In spite of this correction, the original octahedral model persists, and molecular dynamics simulations 3 with this configuration indeed captured most aspects of transient absorption spectra of solvated electrons 4 . Recent resonance Raman studies on aqueous solvated electrons 5,6 showed strongly enhanced, moderately red-shifted intramolecular bending and blue-shifted libration modes compared to bulk water and were also interpreted within the context of the original octahedral model. In this paper, we investigate electron hydration from a different perspective, namely the vibrational spectroscopy of water cluster anions (H 2 O) n -.…”
Section: Manuscriptmentioning
confidence: 91%
“…The experiments by Tauber and Mathies (6,8) and Tahara and coworkers (30) found that the water vibrations that were resonantly enhanced upon excitation of the hydrated electron were virtually identical to those of bulk liquid water, indicating that the hydrated electron's wave function resides predominantly between water molecules and does not significantly perturb the water's electronic structure. The resonance Raman spectrum of water associated with the hydrated electron does show a slight red shift of the bending vibration and a broadening and enhancement on the red side of the O-H stretching vibration; the experimental data from ref.…”
Section: Modeling the Resonance Raman Spectrum Of The Hydrated Electronmentioning
confidence: 99%